Family environment and prosocial behavior tendency of college students: The chain mediating role of empathy and moral sensitivity - Huan Song; Shijie Fan; Yuan Zhao; Yue Wang (PLoS ONE, 2025)
Objectives In order to explore the influence mechanism of family environment on the prosocial behavior tendency of college students and the chain mediating role of empathy and moral sensitivity in this relationship. Methods A survey was conducted on 451 college students using the Family Adaptability and Cohesion scales, the Dispositional Moral Sensitivity Questionnaire, the Prosocial Tendencies Measure and the Chinese Version of the Interpersonal Reactivity Index-C. Results The results showed that empathy and moral sensitivity significantly mediate the effect of family environment on college students’ prosocial behavior tendency. This is manifested in three mediation paths: the mediating role of empathy (with 28.57% of the mediating effect), the mediating role of moral sensitivity (with 61.90% of the mediating effect), and the chain mediating role of empathy and moral sensitivity (with 9.53% of the mediating effect). Conclusions The study reveals the mechanism by which family environment affects college students’ prosocial behavior, which provides some theoretical guidance and practical inspiration for cultivating college students’ prosocial behavior.